Elemental and radiogenic isotope perspective on formation and transformation of cratonic lower crust: Central Slave craton (Canada). (1st June 2020) - Aulbach, Sonja; Symes, Cristen; Chacko, Thomas
Abstract: Kimberlite-borne granulite xenoliths provide rare insights into the age, chemical composition and tectonothermal evolution of the otherwise largely inaccessible deep cratonic crust. The formation and transformation of the lower continental crust (LCC) beneath the central Slave craton (Canada) is here illuminated using whole-rock trace-element and Sr-Nd isotope compositions of nine metabasaltic (MBG), one gabbroic (MGG) and two metasedimentary/hybrid (MSG) granulite xenoliths. On the one hand, published sulphide Re-Os and a few zircon U-Pb data indicate that at least a portion of the LCC beneath the central Slave craton has a Palaeoarchaean origin (∼3.3 Ga), which apparently coincides with a period of juvenile crust and deep lithospheric mantle formation during plume impingement beneath the pre-existing cratonic nucleus. On the other hand, enrichment in Li, Sr, LREE, Pb and Th, but relative depletion in Ti, Hf and HREE, suggest formation of (picro)basaltic protoliths by partial melting of a subduction-modified garnet-bearing source, Crystallisation in the crust after fractionation of plagioclase is inidicated by their Sr and Eu negative anomalies, which are complementary to the positive anomalies in the MGG. Samarium-Nd isotopes in MBG and MGG show large scatter, but fall on Neo- or Mesoarchaean age arrays. These elemental systematics are suggested to fingerprint deserpentinisation fluids plus small amounts of sedimentary melt as the main contaminants of the mantle source, supporting the operation of at least regional and transient subduction at 3.3 Ga. Evidence for quasi-coeval plume impingement and subduction beneath the central Slave craton in the Mesoarchaean is reconcilable in a dynamic regime where vertical tectonics, though waning, was still active and plate interactions became increasingly important. Unradiogenic 87 Sr/ 86 Sr (down to 0.7017) is consistent with significant loss of Rb and probably other heat-producing elements (K, Th, U) plus H2 O during Neoarchaean metamorphism, which helped to enhance LCC viscosity and stabilise the cratonic lithosphere.